1994
DOI: 10.1007/bf01892384
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and chromosomal localization of processed pseudogenes for human RBP-Jk

Abstract: SummaryThe functional gene for human recombination signal sequence-binidng protein (RBP-Jk) and corresponding processed psudogenes have been isolated from various species, such as Drosophila, Xenopus, mouse, and human. Here we report the isolation of another two genomic pseudogenes of human RBP-Jk, named K2 and K7, from a cosmid library of Hela cells. The nucleotide sequences of both genes exhibited more than 95 ~ homology to the functional human gene for RBP-Jk. Moreover, they did not contain any intron seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Amakawa et al (1993) reported that the functional human gene for KBF2/RBP-Jk was assigned to chromosome 3q25 and two pseudogenes IGKJRBP 1 and IGKJR-BP 2 were mapped to 9pt3 and 9q13, respectively. We also reported the similar intense signals of KBF2/RBP-Jk pseudogenes on two sites of chromosome 9p13 and 9q13 (Zhang et al, 1994). Thus, more than four or at least four different genomic pseudogenes of humen KBF2/RBP-Jk may be present in human chromosome.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Amakawa et al (1993) reported that the functional human gene for KBF2/RBP-Jk was assigned to chromosome 3q25 and two pseudogenes IGKJRBP 1 and IGKJR-BP 2 were mapped to 9pt3 and 9q13, respectively. We also reported the similar intense signals of KBF2/RBP-Jk pseudogenes on two sites of chromosome 9p13 and 9q13 (Zhang et al, 1994). Thus, more than four or at least four different genomic pseudogenes of humen KBF2/RBP-Jk may be present in human chromosome.…”
supporting
confidence: 68%
“…Thus, KBF2/ RBP-Jk seems likely to mediate the EBNA2-dependent transactivation of both cellular and viral genes (Zimble et al, 1994). Since the location of the functional gene for RBP-JI~ was reported at human chromosome 3q25 (Amakawa et alo, 1993), while the location was chromosome 9p13 or 9q 13 in the case of pseudogenes (Zhang et al, 1994), we were interested in determining the site(s) of other functional gene(s) for KBF2/RBP-Jk. We found, by FISH (fluorescence in situ hybridization), that the functional gene for KBF2/RBP-Jk was located at chromosome 9p12-13 and 9q13.…”
mentioning
confidence: 99%
“…Recently, Tang et al (1997) corrected this localization and reported that two copies of the functional gene map to chromosome 9p13 → p12 and 9q13, respectively, the same loci which have been described as containing two Rbpsuh pseudogenes (Amakawa et al, 1993 andZhang et al, 1994).…”
Section: Rationale and Significancementioning
confidence: 99%